2013
DOI: 10.1139/cjfr-2012-0491
|View full text |Cite
|
Sign up to set email alerts
|

Developing a general method for the estimation of the fertility rating parameter of the 3-PG model: application in Eucalyptus globulus plantations in northwestern Spain

Abstract: Simple, operational tools are required for forest managers to quantify the effects of soil fertility on tree growth and ecosystem sustainability leading to precise, sustainable forest management. The simplified process-based 3-PG model (Landsberg, J.J., and Waring, R.H., For. Ecol. Manage. 95: 209–228, 1997) provides a useful framework for operational prediction of forest growth. However, no simple objective method for relating the effects of available soil nutrients to the model fertility parameter fertility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 30 publications
0
13
0
3
Order By: Relevance
“…Tuning FR makes detecting the proper value of FR a subjective decision. The validity of 3-PG growth predictions would be improved if a quantitative method could be developed to determine FR based on measured input parameters [6,13]. Determining soil fertility by measuring soil profiles will not always be practical, affordable or accurate for management applications [52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tuning FR makes detecting the proper value of FR a subjective decision. The validity of 3-PG growth predictions would be improved if a quantitative method could be developed to determine FR based on measured input parameters [6,13]. Determining soil fertility by measuring soil profiles will not always be practical, affordable or accurate for management applications [52].…”
Section: Discussionmentioning
confidence: 99%
“…Sampson et al (2008) [12] used clay and sand percentage obtained from State Soil Geograhic Survey (STATSGO) database to predict FR. Vega-Nieva et al (2013) [13] used clay content and Ca, K, and Na in the soil profile to predict FR. Pérez-Cruzado et al (2011) [14] used fertility limitation, water limitation, oxygen limitation, management limitation, and topographic limitation to calibrate FR.…”
Section: Introductionmentioning
confidence: 99%
“…The model has a simple structure, a lower number of parameters than other more detailed physiological models, and it is freely available. 3‐PG has been widely applied to different forest species including several Eucalyptus species (Sands & Landsberg, ; Almeida et al ., ,b, ; Dye et al ., ; Stape et al ., ; Fontes et al ., ; Paul et al ., ; Rodríguez et al ., ; Rodríguez‐Suárez et al ., ; Silva et al ., ; Vega‐Nieva et al ., ). In Spain, Pérez‐Cruzado et al .…”
Section: Introductionmentioning
confidence: 99%
“…In additional studies carried out in commercial plantations, observed volume growth increases always higher than 38% relative to the unfertilized control two years after planting. The recommended doses at planting are summarized in Table 1, which also includes results reported by Merino et al [35] and Vega-Nieva et al [44] and the risk of fertilizer leaching in the rainier regions. Unsurprisingly, responses to mainly N and P were found in the soil with low organic matter content in SW Spain (Mediterranean climate, with rainfall between 450 and 950 mm year´1) [43].…”
Section: Planting Fertilizationmentioning
confidence: 99%